2017
DOI: 10.1016/j.jesp.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Ask in person: You're less persuasive than you think over email

Abstract: Research has found people underestimate the likelihood strangers will comply with their direct requests (Bohns, 2016; Flynn & Lake, 2008). Here we argue this "underestimation-of-compliance effect" may be limited to requests made face-to-face. We find when making direct requests over email, requesters instead overestimate compliance. In two studies, participants asked strangers to comply with requests either face-to-face or over email. Before making these requests, requesters estimated the number of people they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
1
33
0
2
Order By: Relevance
“…This occurred because more Calgary patients received completion requests in person during subsequent follow-up visits; whereas more Edmonton patients were followed-up over email. This finding is consistent with previous studies that found face-to-face requests to be more successful than email requests [ 48 ]. A future sensitivity analysis could be performed to further examine the impact of this difference; however, bias resulting from non-response in surveys is difficult to assess since information about non-responders is rarely available.…”
Section: Discussionsupporting
confidence: 93%
“…This occurred because more Calgary patients received completion requests in person during subsequent follow-up visits; whereas more Edmonton patients were followed-up over email. This finding is consistent with previous studies that found face-to-face requests to be more successful than email requests [ 48 ]. A future sensitivity analysis could be performed to further examine the impact of this difference; however, bias resulting from non-response in surveys is difficult to assess since information about non-responders is rarely available.…”
Section: Discussionsupporting
confidence: 93%
“…The finding that help-seekers underestimate help effort provides an important complement to extant findings that help-seekers underestimate the likelihood that others will comply with their requests for help (Bohns, 2016;Bohns et al, 2011;Bohns et al, 2016;Flynn & Lake (Bohns), 2008;Newark et al, 2014;Roghanizad & Bohns, 2017). Estimations of the likelihood of compliance only tell half the story.…”
Section: Discussionmentioning
confidence: 93%
“…However, research on help-seeking has focused solely on help-seekers' estimations of the likelihood of receiving help, should they request it (Bohns et al, 2011;Bohns et. al., 2016;Flynn & Lake (Bohns), 2008;Newark et al, 2014;Roghanizad & Bohns, 2017). Help-seekers' estimations of the value of that help, should they receive it, have largely been ignored.…”
Section: Help Quality and The Expected Value Of Receiving Helpmentioning
confidence: 99%
See 1 more Smart Citation
“…Written communications have been shown consistently to be less effective or persuasive than face-to-face meetings (Roghanizad and Bohns 2017), and in many cases, telephone conversations may be more productive than email communication. Moreover, do not assume that partners have reliable internet access or that an unanswered email is a lack of interest.…”
Section: Change the Narrativementioning
confidence: 99%